Incidence and determinants of caesarean section in Shiraz, Iran - Zarshenas, M.; Zhao, Yun; Binns, Colin; Scott, Jane (MDPI AG, 2020)
The rate of Caesarean section (CS) without medical indication has increased markedly worldwide in the past decades. This study reports the incidence of CS and identifies the determinants of elective and emergency CS as separate pregnancy outcomes in a cohort of Iranian women. Mothers (n = 700) of healthy, full-term infants were recruited from five maternity hospitals in Shiraz. The association between maternal socio-demographic and biomedical factors with mode of delivery was explored using multivariable, multinomial logistic regression. Most mothers underwent either an elective (35.4%) or emergency (34.7%) CS. After adjustment, women were more likely to deliver by elective CS than vaginally if they were older (≥30 year) compared to younger mothers (<25 year) (Relative Risk Ratio (RRR) 2.22; 95% Confidence Interval (CI) 1.28, 3.84), and had given birth at a private hospital (RRR 3.64; 95% CI 1.79, 7.38). Compared to those educated to primary or lower secondary level, university educated women were more likely to have undergone an elective (RRR 2.65; 95% CI 1.54, 4.58) or an emergency CS (RRR 3.92; 95% CI 2.27, 6.78) than a vaginal delivery. Similarly, overweight or obese women were more likely than healthy weight women to have undergone an elective (RRR 1.91; 95% CI 1.27, 2.87) or an emergency CS (RRR 2.02; 95% CI 1.35, 3.02) than a vaginal delivery. Specialist education of obstetricians and midwives along with financial incentives paid to private hospitals to encourage natural delivery may help in the reduction of unnecessary CS in Iran. In addition, to increase their childbirth knowledge and self-efficacy, pregnant women need to have the opportunity to attend purposefully designed antenatal childbirth preparation classes where they receive evidence-based information on natural childbirth and alternative methods of pain control, as well as the risks and indications for CS.